(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2016)
Colony strength of the Geniotrigona thoracica and Heterotrigona itama colonies were classified into strong, moderate and weak colonies. This colony strength assessment were done based on brood size, workers productivity and workers presence. With this practical guide, uniformity in colony strength can be established for G. thoracica and H. itama colonies and provide a quick references to the Meliponiculturist.